Additive impact of multiple point-of-sale tobacco control policies on youth tobacco-related outcomes - Melody Kingsley; Claude M. Setodji; Joseph D. Pane; William G. Shadel; Glory Song; Lindsay Kephart; Michelle Warner; Patricia Henley; W.W. Sanouri Ursprung (Elsevier, 2022)
Objectives: The tobacco industry utilizes tactics to increase youth awareness, exposure, access and use of tobacco. To address these tactics, municipalities in Massachusetts have passed point-of-sale policies including: 1) restricting flavored tobacco (FTR), 2) restricting cigar package sizes and prices (CPPR), 3) banning tobacco in pharmacies (PB), and 4) raising the minimum legal sales age of tobacco to 21 (MLSA 21). This study evaluated whether more policies, and a combination of policies addressing all three industry tactics, are associated with more favorable youth tobacco-related outcomes. Study design: This study was a cross-sectional survey. Methods: Municipalities were selected based on number of policies and similarity of municipality and tobacco retailer characteristics. The final sample included: Somerville with all four policies, Worcester with two policies (MLSA 21 and PB), and New Bedford with one policy (PB). Surveys were administered to youth in a public high school in each municipality. Multivariable models were used to compare tobacco-related outcomes between municipalities with varying numbers of policies. Results: After adjusting for individual-level demographics, we observed a protective effect of having more policies on flavored tobacco initiation and tobacco exposure and awareness. A protective effect of number of policies on tobacco use was not found, but associations were primarily in the expected direction. Current tobacco users in Somerville had higher odds of menthol use compared to New Bedford. Conclusions: Implementing multiple policies addressing varied industry tactics may be effective for youth tobacco prevention. Including menthol in FTRs may help improve youth tobacco-related outcomes.